The Effectiveness of Wet Cupping Complementary Therapy to Decrease Blood Pressure in Hypertension Patients at Kolaka - Lusiana Jeni; Tahiruddin Tahiruddin; Cholic Harun Rosjidi (KLASICS, 2023)
Abstract. Cupping is one of the complementary therapies that can reduce blood pressure in people with hypertension. Wet cupping therapy is a cupping process by making a fine incision or stabbing to remove dirty blood in the epidermal capillaries and plays a role in controlling vasodilation so that blood pressure can decrease. The purpose of this study was to determine the effectiveness of complementary wet cupping therapy on reducing blood pressure in hypertensive patients at the Pomaala Public Health Center, Kolaka Regency. This study is a quantitative study, with a quasi-experimental design with a "pre-post test design" without a control group which was carried out in June to July 2022. The population in this study was carried out at the Pomalaa Health Center, Kolaka Regency with a total of 25 people. The statistical test method uses 2 different test models, namely the t test for systole and the Wilcoxon for diastole due to the normality test with the results of systole >0.05 and diastole <0.05. The results showed that pre-post obtained p value 0.001< 0.05, on diastolic blood pressure obtained p value 0.001< 0.05 indicating that Ha was accepted. Thus, it can be concluded that there is an effectiveness of complementary wet cupping therapy on reducing blood pressure in hypertensive patients. blood at the Pomalaa Health Center.